The Distinction of Merdeka Curriculum in Madrasah through Differentiated Instruction and P5-PPRA - Syatria Adymas Pranajaya; Azhar Azhar; Muhammad Khairul Rijal; Willy Ramadan (Lembaga Penjaminan Mutu, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2022)
Learning loss is one of the bases for learning recovery policies within a certain period related to the implementation of the curriculum by education units in Indonesia. The government gives options to educational units to implement a curriculum that fits the learning needs of students. The three curriculum options provided are the Curriculum 2013, the Emergency Curriculum (the simplified Curriculum 2013), and the Merdeka Curriculum. The purpose of writing this article is to find out and provide reinforcement regarding the distinction of the Indonesian Government's policy in implementing the Merdeka Curriculum in Madrasah through differentiated instruction and P5-PPRA. This research is in the form of library research by using Government policies, and formal guidelines such as guidelines related to Differentiated Instruction and P5-PPRA as library sources. This research is also supported by articles and eBooks on Google Scholar, Publish and Perish, and Connected Paper. The results of this study have implications for the concept of Merdeka Curriculum in Madrasah with an effort to combine P5-PPRA which is strengthened by differentiated instruction. Apart from being a distinction in Madrasah, this endeavor also has implications for students to